Time course of exercise capacity in patients recovering from COVID-19-associated pneumonia - Elisabetta Zampogna; Nicolino Ambrosino; Laura Saderi; Giovanni Sotgiu; Paola Bottini; Patrizia Pignatti; Rosella Centis; Giovanni Battista Migliori; Antonio Spanevello; Martina Zappa; Dina Visca (Jornal Brasileiro de Pneumologia, 2021)
ABSTRACT Objective: High prevalences of muscle weakness and impaired physical performance in hospitalized patients recovering from COVID-19-associated pneumonia have been reported. Our objective was to determine whether the level of exercise capacity after discharge would affect long-term functional outcomes in these patients. Methods: From three to five weeks after discharge from acute care hospitals (T0), patients underwent a six-minute walk test (6MWT) and were divided into two groups according to the distance walked in percentage of predicted values: <75% group and ≥75% group. At T0 and three months later (T1), patients completed the Short Physical Performance Battery and the Euro Quality of Life Visual Analogue Scale, and pulmonary function and respiratory muscle function were assessed. In addition, a repeat 6MWT was also performed at T1. Results: At T0, 6MWD values and Short Physical Performance Battery scores were lower in the <75% group than in the ≥75% group. No differences were found in the Euro Quality of Life Visual Analogue Scale scores, pulmonary function variables, respiratory muscle function variables, length of hospital stay, or previous treatment. At T1, both groups improved their exercise capacity, but only the subjects in the <75% group showed significant improvements in dyspnea and lower extremity function. Exercise capacity and functional status values returned to predicted values in all of the patients in both groups. Conclusions: Four weeks after discharge, COVID-19 survivors with exercise limitation showed no significant differences in physiological or clinical characteristics or in perceived health status when compared with patients without exercise limitation. Three months later, those patients recovered their exercise capacity.